From the Grand Tour to the European Voyages of Ion Codru Drăguşanu - MĂRCUŞ, Cornel-Dănuţ (Studia Universitatis Babeș-Bolyai Historia, 2016)
From the Grand Tour to the European Voyages of Ion Codru Drăguşanu realities. The study analyzes the five European journeys made by Ion Codru Drăguşanu in the first half of the 19th century. The travel routes are analyzed from the perspective of the information provided by the author, but also from other relevant sources which help to identify the participants of the journeys, the names of whom are not rendered by the author, and who until now had been mistakenly identified. We note the trend of coordinating the timeframe of the trip with the event calendar of a certain place, events that become prime attractions for our traveler. The imagology analysis identifies the scenes rendered by the author, presented from a comparative standpoint, aiming at showing similar images depicted by other travelers, European and Romanian, which in itself become the evidence of their transmission. We note the evolving nature of these images, from the volume that had been published in 1865, to the letters published subsequently, in 1869 and 1879 - dates which represent the time the letters were in fact published, and not the timeframe of the travels themselves. The study demonstrates that, in formal terms, certain journeys may be assigned to „Grand Tour” type travels, but most of the images portrayed during the trips fall under the umbrella of the Romantic journey, laced with accents borrowed from the realist movement. Rezumat: De la „Grand Tour” la călătoriile europene ale lui Ion Codru Drăguşa-nu. Studiul analizează cele cinci călătorii europene realizate de Ion Codru Drăgu-şanu, în prima jumătate a secolului al XIX-lea. Itinerariile călătoriilor sunt urmări-te din perspectiva informaţiilor oferite de autor, dar şi din cea a altor surse, care ajută la identificarea participanţilor la călătorie, al căror nume autorul nu îl redă, dar pe care am reuşit să îi identificăm pentru prima oară. Este surprinsă practica de coordonare temporală a călătoriilor cu participarea la anumite evenimente, care devin atracţii de prim rang pentru călătorul nostru. Analiza imagologică identifică imaginile transmise de autor, urmărite într-o manieră comparativă, urmărindu-se existenţa unor imagini similare la alţi călători, europeni sau români, ceea ce devine o dovadă de transmitere a acestora. Se remarcă caracterul evolutiv al acestor imagini, de la volumul apărut în 1865, până la scrisorile publicate ulterior, în 1869 şi 1879, astfel că acestea aparţin perioadei publicării, nu realizării călătoriilor. Studiul demonstrează faptul că, din punct de vedere formal, unele călătorii pot fi atribuite celei de tip „Grand Tour”, dar cele mai multe imagini ale călătoriei se raportează călătoriei romantice, în care găsim accente ale curentului realist. Cuvinte-cheie: Ion Codru Drăguşanu, călătorii, Grand Tour, imagologie, turism, romantism